Pemetaan Kualitas Visual Lanskap Pada Daya Tarik Wisata Di Kebun Raya Eka Karya Bedugul - Dwijaksara, I Gusti Bagus Agung; Asmiwyati, I Gusti Agung Ayu Rai; Sukewijaya, I Made (Jurnal Arsitektur Lansekap, 2021)
The visual landscape quality mapping of tourist attraction in Eka Karya Bedugul Botanical Garden. Eka Karya Bedugul Botanical Garden is a national and international reference to the ex-situ conservation of tropical mountain plant and botanical aspect service, environmental education, horticulture, landscape and tourisms. In order to provide tourism services, actual activities such as conserving and improving the quality of view are needed. The beauty of landscape view is not only determined by enviromental characteristic and landscape wealth, but it also is determined through the assessment of people from their perception over a landscape. The research aimed to map the visual quality landscape in Eka Karya Bedugul Botanical Garden and determine the best criteria of visual quality on natural landscape. The research methods used were surverys and visual assesments which include data collecting step, beauty assesment with scenic beauty estimation (SBE), and descriptive analysis about the determinant factor of visual quality on natural landscape. The beauty of the visual quality over the natural landscape was shown through the harmonic combination of landscape form elements. The visual quality over the natural landscape used were the unity of resources, well maintained natural landscape, and giving a lively effect resulted through the use of combining landscape form elements and design. There were seven landscape points that fall under the best visual quality landscape category, which were landscape number 18,32,33,34,37,38, and 40. The visual landscape quality points in Eka Karya Bedugul Botanical Garden need a regular and persistence maintainence to extend the longevity and aesthetic quality of the natural landscape.